Education on preventing diabetes mellitus for prolanis through the introduction of high-fiber foods and glycemic index variations - Sudrajah Warajati Kisnawaty; Munitya Anjalya Pertiwi; Ima Ariyani; Fitriana Mustikaningrum (Community Empowerment, 2023)
Most members of Prolanis at Ngemplak 1 Community Health Center in Sleman Regency suffer from diabetes mellitus (DM). One therapy for individuals with DM is to maintain a healthy eating pattern. Consuming high-fiber foods and those with a low to moderate glycemic index can help in maintaining normal blood glucose levels. The aim of this program is to enhance the knowledge of Prolanis members about high-fiber foods and variations in the glycemic index to prevent DM. Programs include surveys, problem identification, counseling using booklets, and evaluation. Based on the evaluation results, this program successfully increased Prolanis members' knowledge by 44.6% regarding high-fiber foods and variations in the glycemic index.